Couple Burnout and Partner's Substance-Dependency: Is there any Association? - Zeinab Haghparast; Hedyeh Riazi; Jamal Shams; Ali Montazeri (SAGE Publishing, 2023)
Objectives Substance-dependency is a significant health problem that might affect couples' relationships and lead to several complications such as burnout. This study aimed to assess and compare couple burnout in women with and without substance-dependent partners. Methods In this cross-sectional study samples of women with and without substance-dependent partners were studied. Couple burnout was assessed using the Couple Burnout Measure (CBM). The data then were compared between the study groups by performing descriptive statistics, independent t-test, and chi-square. Logistic regression analysis was carried out to examine the association between couple burnout and independent variables. Results In all 264 women with (n = 121) and without (n = 143) substance-dependent partners were studied. Couple burnout was assessed using the Couple Burnout Measure (CBM). There were significant differences between both groups in most characteristics. The mean score of couple burnout in women with and without substance-dependent partners were 3.8 ± 1.2 and 2.6 ± 0.85 respectively (p < 0.001). In logistic regression analysis, the probability of couple burnout in women with substance-dependent partners was 4.5 times more than those without substance-dependent partners (OR = 4.50, CI = 2.48-8.17, p < 0.001). Conclusion The findings showed that women with substance-dependent partners might suffer from higher couple burnout. Indeed, implementing appropriate interventions such as educational and counseling programs in health centers and substance abuse treatment centers is recommended. In fact, the current study highlights the extra burden that women with substance-dependent partners experience.